A Biocompatible Multilayer Film from an Asymmetric Picolinium‐Containing Polycation with Fast Visible‐Light/NIR‐Degradability. Issue 22 (25th September 2019) - Zhang, Hanzhi; Zhou, Tongtong; Shen, Jiwei; Zhang, Ping; Chen, Xin; Chen, Yongming; Yu, You
Abstract: Finely tuning the photodegradation behavior of the layer‐by‐layer (LbL) film from the view of controlling the chemical structure of the film‐building polymer is still a challenge in related fields. To meet this requirement, a photodegradable polymer (P1) is rationally designed for assembling a visible‐light‐degradable multilayer film with polystyrene sulfonate (PSS). Compared with similar photopolymers (P2 and P3), this asymmetric picolinium‐containing polymer can significantly enhance the degradation rate of as‐prepared LbL films; under the same degradation condition, the degradation rate of (P1/PSS)10 is 3 and 6.6 times that of (P2/PSS)10 and (P3/PSS)10, respectively. Moreover, near‐infrared light (NIR) is available for triggering the degradation of this film with the assistance of upconversion nanoparticles of YbTm@Lu. The cell cytotoxicity and cell proliferation experiments reveal that P1 is nontoxic and favorable for cell proliferation at concentrations of up to 500 μg mL −1 . As for (PSS/P1)10 films, the ratio of cell number of these two samples ((PSS/P1)10 modified: photodegraded) increases dramatically and reaches about 1.67:1 after 72 h incubation. On the basis of these results, it is anticipated that P1 and this LbL film is an exceptional candidate for visible‐light/NIR degradable materials in materials and biological science, medicine, and optics. Abstract : A fast visible‐light/near‐infrared light degradable multilayer film is for the first time fabricated by using an asymmetric photolabile picolinium‐containing polycation as the building block, which is biocompatible, has low toxicity, and is available for selectively promoting the cell proliferation via simply controlling its degradation process, showing potential applications in smart materials and cell biology.